2018
DOI: 10.1111/pedi.12712
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent type 2 diabetes: Comparing the Pediatric Diabetes Consortium and Germany/Austria/Luxemburg Pediatric Diabetes Prospective registries

Abstract: Both DPV and PDC youth have multiple risks for diabetes complications. Understanding reasons for persistently higher HbA1c in PDC youth requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
(58 reference statements)
2
5
0
1
Order By: Relevance
“…Almost half of the children (46.5%) were started on insulin treatment at the time of diagnosis and 40.5% were started on metformin alone. The high rate of medical therapy was similar to the other paediatric cohorts in the USA and Europe (85 and 86%, respectively) . Fasting blood glucose and HbA 1C levels of children who were treated with insulin or a combination of insulin and metformin were significantly higher than those who were not treated with insulin, suggesting that physicians mostly follow International Society for Pediatric and Adolescent Diabetes (ISPAD) guidelines for the treatment of Type 2 diabetes.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Almost half of the children (46.5%) were started on insulin treatment at the time of diagnosis and 40.5% were started on metformin alone. The high rate of medical therapy was similar to the other paediatric cohorts in the USA and Europe (85 and 86%, respectively) . Fasting blood glucose and HbA 1C levels of children who were treated with insulin or a combination of insulin and metformin were significantly higher than those who were not treated with insulin, suggesting that physicians mostly follow International Society for Pediatric and Adolescent Diabetes (ISPAD) guidelines for the treatment of Type 2 diabetes.…”
Section: Discussionsupporting
confidence: 63%
“…To date, a female preponderance has been shown in all paediatric Type 2 diabetes cohorts . The majority (68%) of children in the current study were also female.…”
Section: Discussionsupporting
confidence: 48%
“…In YDR and SEARCH, 30–43% of type 2 diabetes patients were treated with metformin only, and 33–39% required insulin treatment 28 . Similar to the SEARCH study, the Pediatric Diabetes Consortium, which included young type 2 diabetes patients from 19 centers in the USA, reported an average HbA 1c of 7.8%, whereas the Pediatric Diabetes Prospective registries in Germany, Austria and Luxemburg reported a lower mean HbA 1c of 6.5% 24 . In the present study, 50% of type 2 diabetes patients were treated with an oral antidiabetic agent only.…”
Section: Discussionmentioning
confidence: 94%
“…The similar ages of onset between male and female Chinese patients further confirmed that the increased levels of insulin resistance during puberty only had a limited effect on the pathogenesis of T2DM. Furthermore, only 58% of patients with T2DM were obese in this study, and the obesity rate in China is significantly lower than that in Europe[ 32 ]. It was noticed that even little weight gain could cause insulin resistance and increased risk of diabetes among the Chinese population[ 15 ].…”
Section: Discussionmentioning
confidence: 96%